Identifikasi Potentially Inappropriate Medication (PIM’s) Menggunakan Kriteria Beers dan STOPP pada Pasien Geriatri dengan Diagnosis Gastrointestinal Rawat Inap di RSUD Abdul Wahab Sjahranie Samarinda: Identification of Potentially Inappropriate Medication (PIM’s) Using Beers and STOPP Criteria in Geriatric Patients with Gastrointestinal Diagnosis at Abdul Wahab Sjahranie Samarinda Hospital - Rahmayunitha Muriana; Maria Almeida; Adam M. Ramadhan (Proceeding of Mulawarman Pharmaceuticals Conferences, 2023)
The Beers and STOPP criteria are criteria used to identify possible inappropriate treatment including drugs that should be avoided and used in patients older than 65 years. These two criteria are a reference in evaluating the prescription of potentially inappropriate medications or Potentially Inappropriate Medications (PIM's) in geriatrics. The aim of the research is to determine geriatric characteristics, treatment profiles in prescribing and PIM's based on the Beers criteria and STOPP criteria in geriatric patients with gastrointestinal diagnoses who are hospitalized at Abdul Wahab Sjahranie Hospital, Samarinda. This research used an observational research design with data collected retrospectively and analyzed descriptively. The research results obtained from 80 patient data showed that geriatric patients were predominantly female as many as 47 patients (59%) with young elderly aged 65 - 74 years as many as 53 patients (66.25%) with the most dominant diagnosis being diarrhea and dyspepsia as many as 36 patients (42.85%) and the most common comorbidity was hypertension in 17 patients (30.35%). The most dominant use of medication in geriatric patients was antiemetic therapy, 64 patients (80%). Based on PIM's analysis using the Beers and STOPP criteria, no events were found according to the Beers criteria and of the 23 cases included in drug use, only 1 incident was found using the STOPP criteria. Keywords: Beers, Geriatric, STOPP, Potentially inappropriate medication (PIM’s) Abstrak Kriteria Beers dan STOPP adalah kriteria yang digunakan untuk mengidentifikasi kemungkinan pengobatan yang tidak tepat termasuk obat yang harus dihindari dan digunakan pada pasien yang berusia lebih dari 65 tahun. Kedua kriteria ini menjadi acuan dalam mengevaluasi peresepan obat yang berpotensi tidak tepat penggunaannya atau Potentially Inappropriate Medication (PIM’s) pada geriatri. Tujuan penelitian yaitu mengetahui karakteristik geriatri, profil pengobatan pada peresepan serta PIM’s berdasarkan kriteria Beers dan kriteria STOPP pada pasien geriatri dengan diagnosis gastrointestinal rawat inap di RSUD Abdul Wahab Sjahranie Samarinda. Penelitian ini menggunakan rancangan penelitian observasional dengan pengambilan data secara retrospektif dan dianalisis secara deskriptif. Hasil penelitian yang diperoleh dari 80 data pasien menunjukkan bahwa pasien geriatri dominan Perempuan sebanyak 47 pasien (59%) dengan usia lansia muda 65 – 74 tahun sebanyak 53 pasien (66.25%) dengan diagnosis paling dominan diare dan dispepsia sebanyak 36 pasien (42.85%) dan penyakit penyerta terbanyak adalah hipertensi sebanyak 17 pasien (30.35%). Penggunaan obat pada pasien geriatri paling dominan adalah terapi antiemetik sebanyak 64 pasien (80%). Berdasarkan analisis PIM’s menggunakan kriteria Beers dan STOPP, tidak ditemukan kejadian pada kriteria Beers dan dari 23 kasus yang masuk dalam penggunaan obat hanya ditemukan 1 kejadian dengan kriteria STOPP. Kata Kunci: Beers, Geriatri, STOPP, Potentially inappropriate medication (PIM’s)